Gene–Gene Interactions Among PRKCA, NOS3 and BDKRB2 Polymorphisms Affect the Antihypertensive Effects of Enalapril - Oliveira‐Paula, Gustavo H.; Luizon, Marcelo R.; Lacchini, Riccardo; Fontana, Vanessa; Silva, Pamela S.; Biagi, Celso; Tanus‐Santos, Jose E. (Basic & clinical pharmacology & toxicology, 2017)
Protein kinase C (PKC) signalling is critically involved in the control of blood pressure. Angiotensin‐converting enzyme inhibitors (ACEi) affect PKC expression and activity, which are partially associated with the responses to ACEi. We examined whether PRKCA (protein kinase C, alpha) polymorphisms (rs887797 C>T, rs1010544 T>C and rs16960228 G>A), or haplotypes, and gene–gene interactions within the ACEi pathway affect the antihypertensive responses in 104 hypertensive patients treated with enalapril as monotherapy. Patients were classified as poor responders (PR) or good responders (GR) to enalapril if their changes in mean arterial pressure were lower or higher than the median value, respectively. Multi‐factor dimensionality reduction was used to characterize interactions among PRKCA, NOS3 (nitric oxide synthase 3) and BDKRB2 (bradykinin receptor B2) polymorphisms. The TC+CC genotypes for the rs1010544 polymorphism were more frequent in GR than in PR (p = 0.037). Conversely, the GA+AA genotypes for the rs16960228 polymorphism, and the CTA haplotype, were more frequent in PR than in GR (p = 0.040 and p = 0.008, respectively). Moreover, the GG genotype for the PRKCA rs16960228 polymorphism was associated with PR or GR depending on the genotypes for the rs2070744 (NOS3) and rs1799722 (BDKRB2) polymorphisms (p = 0.012). Our results suggest that PRKCA polymorphisms and gene–gene interactions within the ACEi pathway affect the antihypertensive responses to enalapril.